2018
DOI: 10.1186/s12886-018-0792-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of endoscopic trans-ethmosphenoid optic canal decompression for indirect traumatic optic neuropathy in children

Abstract: BackgroundTo evaluate the safety and outcomes of endoscopic trans-ethmosphenoid optic canal decompression (ETOCD) for children with indirect traumatic optic neuropathy (ITON).MethodsFrom July 1st, 2008 to July 1st, 2015, 62 children diagnosed with ITON who underwent ETOCD were reviewed. Main outcome measure was improvement in visual acuity after treatment.ResultsAltogether 62 children (62 eyes) with a mean age of 11.26 ± 4.14 years were included. Thirty-three (53.2%) of them had residual vision before surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…A specific injury factor, such as a head injury and stroke, causes damage to the brain tissue, often causing cognitive dysfunction in the patient, resulting in difficulty in perceiving the patient and adapting to the external environment. Life and society can live independently, work hard, and even constitute obstacles [ 1 , 2 ]. Various cognitive dysfunctions appear in the human head after trauma, such as emotional disturbance, memory loss, and decreased concentration.…”
Section: Introductionmentioning
confidence: 99%
“…A specific injury factor, such as a head injury and stroke, causes damage to the brain tissue, often causing cognitive dysfunction in the patient, resulting in difficulty in perceiving the patient and adapting to the external environment. Life and society can live independently, work hard, and even constitute obstacles [ 1 , 2 ]. Various cognitive dysfunctions appear in the human head after trauma, such as emotional disturbance, memory loss, and decreased concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no effective treatment is available for TON ( Chaon and Lee, 2015 ; Singman et al, 2016 ; Yan et al, 2016 ). The clinical treatment options for TON include observation (conservative management), high-dose corticosteroid treatment, or surgery (optic canal decompression), which are based on studies on small patient cohorts ( Goldberg and Steinsapir, 1996 ; Yu-Wai-Man and Griffiths, 2013 ; Yan et al, 2016 ; Yu et al, 2016 ; Kashkouli et al, 2017 ). In comparative nonrandomized studies on the treatment outcomes in patients with TON, the results showed no clear effect of either hormonal therapy or surgical treatment ( Levin et al, 1999 ; Carta et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased intracanalicular pressure after an injury is considered to be one of the main pathophysiological manifestations. 2…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous studies showed that independent factors for VA prognosis were time interval between injury and treatment, degree of visual loss, optic canal fracture, orbital fracture, and hemorrhage in the post-ethmoid or sphenoid sinus. 2,12,13…”
Section: Introductionmentioning
confidence: 99%